Analisis efektivitas metode pembelajaran daring - Setiawan, Devina Permata (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
During the Coronavirus pandemic now it has an impact on people's daily lives in their activities. One of the perceived impacts is on education. This is because it requires students and students to learn from home or online (daring). The full online method on every campus is the first time conducted in Indonesia. Inadequate advice and infrastructure, such as the unavailability of internet throughout Indonesia and the unstable quality of the internet. The exact sciences and science fields focus on practical learning, giving rise to a polemic whether online methods can improve the quality of self-potential in every student. Therefore, this study aims to look at the effectiveness of daring methods for students in the exact sciences field at the Universitas Islam Indonesia. The analysis was performed using primary data by distributing questionnaires and the method used was ordinal regression analysis. Based on the results of the analysis found that daring learning is considered less effective in teaching and learning.